ANALYSIS OF ENVIRONMENT USE AND BEHAVIOR OF BUBO BUBO IN THE WESTERN TIEN SHAN, SHAKPAK PASS USING GPS/GSM TELEMETRY (ҚазҰУ хабаршысы. Экология сериясы, 2024)
The study focuses on the habitat use and behavioral characteristics of the Eurasian eagle-owl (Bubo bubo) at Shakpak Pass, located in the Western Tien Shan. This work is the first detailed research on the spatial behavior and habitat use of this species in this vital migratory corridor. The goal was to map the tagged Eurasian eagle-owl's range, identify habitat preferences, and analyze behavioral adaptations using a mixed-methods approach that combines quantitative GPS tracking with qualitative behavioral observations.The findings show the eagle owl's significant localization of movements, demonstrating its attachment to specific nesting and hunting territories. The analysis reveals the eagle owl's capacity to adapt to various hunting and roosting habitats, indicating a high degree of ecological plasticity. Distinct diurnal and nocturnal activity patterns were identified, highlighting the owl’s specific hunting times and preferred habitats, ranging from open areas to rugged terrains.The temperature analysis and daily activity tracking over nine days show that the eagle owl is more active at lower temperatures, particularly at sunset and dawn, with peak activity periods from 7 pm to 11 pm and during dawn hours from 4 am to 7 am. This research provides valuable insights into the behavioral ecology of the Eurasian eagle-owl. The findings hold practical significance for avian ecology and conservation science and can be useful for future research in the Tien Shan and analogous ecosystems.Keywords: Bubo bubo, bird behavior, nocturnal birds, GPS telemetry, GSM transmitter, habitat use, bird conservation.